Examining the relationship of flow experience and athletes' trait characteristics - Stavrou, N. A.; Karakasidou, E.; Psychountaki, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Flow experience has been used in psychology in order to describe an intrinsically rewarding experience that athletes` feel during high levels of performance. Flow is experienced by an athlete when the goals are clearly set, when he/she is completely and concentrated on the task at hand, feels a sense of control over his/her actions, perceives the task as self-rewarding, and his/her actions look effortlessly and automatically (Jackson, 1992). An important issue associated with the generation of flow is whether particular situational or personal characteristics facilitate the experience of flow (Kimiecik & Stein, 1992). Based on that, the purpose of the study is to examine whether athlete`s trait general and competitive characteristics constitute significant predictors of flow experience. Methods: Three hundred and fifty one (351) (mean age = Ì = 18.14, SD = 5.37) athletes participated in the study. In non-competitive situations, based on how they usually felt, the athletes completed the following instruments: (1) Dispositional Flow Scale-2, (2) Trait Anxiety Inventory, (3) Self-Esteem Scale, (4) Sport-Competition Anxiety Test, (5) Trait-Sport Confidence Inventory and (6) Competitive Worries Inventory. Results: General trait anxiety indicated negative correlations with flow experience, as well as, competitive trait anxiety. On the other hand, significant positive correlations revealed between self-esteem (rmean = .33) and trait self-confidence (rmean = .39) with athletes` flow experience. Hierarchical regression analysis (1st step: general trait characteristics, 2nd step: competitive trait characteristics) indicated that general (R2 adjusted = .437, F = 16.110, p<.001) and competitive variables (R2 adjusted = .422, F = 4.554, p<.001) constitute significant predictors of flow experience. Discussion: Self-esteem and self-confidence suggested a close positive relationship to flow experience compared to the negative characteristics, such as general and competitive anxiety, as well as, competitive worries. Thus, if an athlete feels confidence about his/her sport ability, this is associated with achieving high levels of flow experience. On the other hand, the lack of relationship between the trait anxiety ratings and the flow subscales suggests that this variable may not be as relevant to flow experiences as selfesteem. In addition, based on the regression analysis results, positive emotional characteristics constitute significant predictors of flow experience, while, negative emotional characteristics did constitute significant predictors of global flow factor.